2017
DOI: 10.1111/1744-7917.12486
|View full text |Cite
|
Sign up to set email alerts
|

New insight into foregut functions of xenobiotic detoxification in the cockroach Periplaneta americana

Abstract: The physiological functions of insect foregut, especially in xenobiotic detoxification, are scarcely reported because of unimportance in appearance and insufficient molecular information. The cockroach Periplaneta americana, an entomological model organism, provides perfect material to study physiological functions of foregut tissue due to its architectural feature. Through Illumina sequencing of foregut tissue from P. americana individuals (control) or insects treated with cycloxaprid, as a novel neonicotinoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…In addition to insecticide induction assays, investigating tissue-specific expression patterns could also further contribute to the identification of resistance gene functions. Usually, detoxification genes are abundant in insect tissues such as Malpighian tubule, midgut, and fat body and play an important role in insecticide resistance. , In Plutella xylostella, PxGSTu is highly expressed in the Malpighian tubule and midgut and directly metabolizes chlorantraniliprole . Similarly, it has also been shown that resistance-related P450s genes are abundant in the Malpighian tubule and midgut with clothianidin resistance in Bradysia odoriphaga .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to insecticide induction assays, investigating tissue-specific expression patterns could also further contribute to the identification of resistance gene functions. Usually, detoxification genes are abundant in insect tissues such as Malpighian tubule, midgut, and fat body and play an important role in insecticide resistance. , In Plutella xylostella, PxGSTu is highly expressed in the Malpighian tubule and midgut and directly metabolizes chlorantraniliprole . Similarly, it has also been shown that resistance-related P450s genes are abundant in the Malpighian tubule and midgut with clothianidin resistance in Bradysia odoriphaga .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lipophilic insecticides have been shown to be taken up into foregut tissue of the honeybee Apis mellifera ( Conner et al, 1978 ). The foregut may even play a role in insecticide detoxification, as treatment of the cockroach Periplaneta americana with the neonicotinoid insecticide cycloxaprid resulted in an upregulation of 22 putative xenobiotic detoxification genes in foregut tissue ( Zhang et al, 2018 ). Another study proposed that a sugar receptor that is strongly expressed in the foregut of larvae of the cotton bollworm Helicoverpa armigera (Noctuidae) is involved in regulating feeding behavior ( Xu et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…furcifera and the cockroach P. Americana, respectively. However, in this study, only one CYP450 gene (CYP338) was upregulated in O.…”
Section: Discussionmentioning
confidence: 99%
“…For the white-backed planthopper Sogatella furcifera, 10 cytochrome P450 monooxygenase (CYP450) genes, 1 microsomal glutathione S-transferase (GST) gene, and 1 acetylcholinesterase gene were upregulated in response to a high-dose CYC treatment, whereas 5 CYP450 genes, 1 GST gene, and 2 carboxylesterase genes were upregulated in response to a low-dose CYC treatment . For the cockroach Periplaneta americana, 18 CYP450 genes, 1 GST gene, and 2 carboxylesterase genes were upregulated after a CYC treatment . In addition to target alteration and metabolic enhancement, penetration resistance is also a common mechanism of insecticide tolerance or resistance. However, the genes involved in cuticle penetration have not been investigated in CYC-treated insects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation